SEMIOTIKA MASKULINITAS DAN FEMINITAS STUDI ATAS KONSTRUKSI GAYA HIDUP DAN IDENTITAS GENDER DALAM IKLAN: Alifia Oktrina Fayardi, Abdul Firman Ashaf - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
Lifestyle which attached to daily life has become a necessity for men and women. Lifestyle in advertisements often made the audience interested to follow it up. The audiences were made to consume products that were advertised to achieve the ideal lifestyle depicted in the ads. The aim of this study was to determine the lifestyle of men and women in men's product advertisements and women's product advertisements and also how the construction process. Methods and theories that were used in this study were semiotics of Roland Barthes. This study found that men’s product advertisements emphasized men’s lifestyle with masculine image. Women’s product advertisements instilled women’s lifestyle attached to appearances. Ads also brought new habits both for men and women as part of their lifestyle. Ads looked like to dictate people's lifestyles by providing an idea of how a person should look, what to eat, and how to spend leisure